Técnicas para sexagem precoce em pacamã (Lophiosilurus alexandri, Steindachner, 1876) - Reinaldo Melillo Filho (2016)
This study aimed to evaluate sexing techniques for juvenile Lophiosilurus alexandri. The following techniques were tested: Coelioscopy, performed with the use of video surgery equipment; coeliotomy, consisting of a surgical procedure for direct visualisation of the gonads, and sex determination by a urethral probe, based on sex identification by the comparison between the genital papillae. Using coelioscopy, survival was 100%, 30 days after the procedure. The fish restarted eating 10 days after surgery. This technique presented 100% confirmation for individuals identified as females, while for those identified as males confirmation was 66.6%. There was no significant difference between males and females for anesthesia induction and recovery time. However, the procedure took longer for males due to the difficulty in observing the gonads, which can be attributed to the large amount of visceral fat in males and to an intestinal coefficient larger than 1, despite it being a carnivorous fish. The gonadosomatic index was higher in females. As for the coeliotomy technique, 30 days after surgery, the survival rate was also 100%. Two intersex animals were found. This technique was efficient for sexing males with 96.3% accuracy and females with 93.9% accuracy. The fish restarted eating between 10 and 14 days after surgery. Significant differences between males and females were not found for anesthesia induction time, duration of the surgical procedure to visualise the gonads and anesthesia recovery time (p > 0.05). The urethral probe technique was less efficient, with 67.8 and 81.8% accuracy for males and females, respectively. We conclude that coeliotomy is recommended for sexing L. alexandri juvenile and coelioscopy, to identify females of L. alexandri juvenile.